2005
DOI: 10.1158/0008-5472.can-05-0713
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Induced K-ras Mutations in Human Colorectal Cancer Cells: Role of Microenvironmental Regulation of MSH2 Expression

Abstract: Mutation of the K-ras gene is one of the most common genetic alterations in solid tumors, including colorectal cancer. The relatively late emergence of K-ras mutations in colorectal cancer is particularly striking in the class of mismatch repair-deficient tumors associated with earlyonset microsatellite instability. We, therefore, tested the hypothesis that the microsatellite instability phenotype itself does not efficiently trigger K-ras mutations in colorectal cancer cells, but rather that tumor-associated m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 40 publications
4
49
1
1
Order By: Relevance
“…While originally reported to be non-tumorigenic (Shirasawa et al, 1993) in our hands these cells demonstrate attenuated tumorigenicity (Shahrzad et al, 2005), and in this study formed palpable tumors in all mice 45 days after subcutaneous injection of 2 Â 10 6 cells into the right flank of RAG-1 null mice. When the average tumor size reached 35 mm 3 mice were randomized into treatment and control groups and subjected to low-dose (metronomic) cyclophosphamide (LDM) for a period of 2 weeks followed by a 2-week break period.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…While originally reported to be non-tumorigenic (Shirasawa et al, 1993) in our hands these cells demonstrate attenuated tumorigenicity (Shahrzad et al, 2005), and in this study formed palpable tumors in all mice 45 days after subcutaneous injection of 2 Â 10 6 cells into the right flank of RAG-1 null mice. When the average tumor size reached 35 mm 3 mice were randomized into treatment and control groups and subjected to low-dose (metronomic) cyclophosphamide (LDM) for a period of 2 weeks followed by a 2-week break period.…”
Section: Resultssupporting
confidence: 58%
“…Since we had previously shown that K-ras wt/null Dks-8 xenografts develop mutations in codon 13 of this oncogene (Shahrzad et al, 2005), we explored the possibility that this event may have been enhanced in treated tumors.…”
Section: Ldm-induced Tumor Hypoxiamentioning
confidence: 99%
See 3 more Smart Citations